Intracardiac KCl Injection in Cesarean Scar Pregnancy: A Review Article (Nepalese Journal of Radiology, 2023)
Embryo implantation in a previous caesarean scar (CS) resulting in a caesarean scar pregnancy (CSP) is another rare but potentially catastrophic complication of a previous caesarean birth. CSP can be detected between days 33 and 94 of pregnancy. Methotrexate and potassium chloride (KCl) are the most common feticidal agents used. intracardiac KCl causes feticide and reduces the uteroplacental blood flow, thereby decreasing the rate of hemorrhage due to placenta previa, caesarian scar pregnancy and in cases of fibroids; it is easy to evacuate the macerated fetus. Intracardiac KCl causes feticide and reduces the uteroplacental blood flow, thereby decreasing the rate of hemorrhage and abortion time before termination of pregnancy (TOP) leading to an easy evacuation of the macerated fetus. In conclusion, feticide with intracardiac KCl is a safe procedure.